Analysis of Slang Words in Selected Song by “Charlie Puth” - Ni Nyoman Cintya Pradnyani; Ni Wayan Suastini (CV Wahana Publikasi, 2023)
In today’s society, slang terms are often used in communication. Slang is a colloquial form of language used to shorten and simplify communication. The purpose of this study is to analyze the slang words contained in Charlie Puth’s selected song. Based on Yule’s theory, this study examines the process of slang creation (1895: 51-55). This study makes use of the Chapman-proposed primary class of slang words (2007: 8). The approach used in this study is a qualitative descriptive method in order to make the data used and the research problem clear. The information was gathered by reading the song lyrics, scanning them for slang terms, and then making a note of those terms that were included in Charlie Puth’s song lyrics. The results of this study indicate there are 18 main slang words found in 8 song lyrics by Charlie Puth. In this study can be found 4 Blending, 8 Clipping, 1 Compounding, 2 Coinage, 1 Borrowing, and 2 Acronym. In this study, because using the clipping process makes words simpler, faster, and quicker to explain things, slang terms are often used in song lyrics.